PENGAWASAN DPR-RI DALAM BISNIS MILITER SEBAGAI BAGIAN DARI REFORMASI TENTARA NASIONAL INDONESIA (TNI) - Djuyandi, Yusa (Departemen Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2016)
DPR-RI oversight in TNI (military) Business have very important role in forming of professional and reliable TNI, despitefully DPR-RI oversight also useful to link citizen priority and views in rule of policy and law in defence area. The purpose of this research is to analyze the oversight mechanism conducted by DPR-RI in the case of military business. Theory used by researcher in conducting this research is theory of parliamentary oversight, which is conducting through various mechanism which available in parliament, that is: passing debate mechanism; passing existence of commission; and through raised questions when in meeting. This research used qualitative method,and data research was obtained from primary and secondary data. Primary data was gained through observation and interview. Based on the research, the oversight mechanism have been run by first commission of DPR-RI was still weaken, on the other side the parliament (DPR) also lack in creating an effective oversight, where this matter because of some factors, such as: the lack of political willingness of parliamentary member, lack of positive supervision practices and the limited information had by DPR.